RHD exon 5, 7 and 10 targeted non-invasive prenatal screening of fetal Rhesus-D (RhD) in selected RhD negative pregnant women in Ethiopia. - Birhanu Niguse (PLoS ONE, 2022)
Background A majority of non-invasive prenatal screening studies determining fetal RhD status have been tested on Caucasian and Asian populations, but limited or no studies have been conducted on the Ethiopian population. In the current study, we carried non-invasive prenatal screening of fetal RHD genotype in selected RhD negative Ethiopian pregnant women. Methods Cell-free DNA was extracted from the plasma samples of 117 RhD pregnant women between 9 and 38 weeks of gestation. Fetal RHD genotypes were detected by targeting exons 5, 7 and 10 of the RHD gene by using real-time PCR assay. RHD genotypic results were confirmed by neonatal cord blood serology. Results Fetal RHD genotyping was conclusive in all 117 subjects. RHD genotype was correctly predicted in 115 of 117 cases, thus the test yielded 98.3% accuracy (95%CI: 97.3-99.1%). Among 115 cases, 105 were genotyped as RHD positive and 12 were genotyped as RHD negative. The sensitivity and specificity of the test were 99.1% (95% CI: 94.8-99.9%) and 91.7% (95%CI: 61.5-99.7%) respectively. The negative and positive predictive values were 99.9% (95%CI: 99.2-99.9%) and 54.0% (95% CI: 15.2-88.4%) respectively. SRY genotyping results were in complete concordance with fetal sex. Conclusion Multi exon targeted non-invasive prenatal screening test for fetal RhD determination exhibited high accuracy and sensitivity. A confirmatory study with a bigger size of study subjects is warranted before enabling clinical implementation.